Mantras in Malay Traditional Healing in Kedah: An Analysis from the Perspective of the Islamic Faith: (Mantera dalam Perawatan Tradisional Melayu di Kedah: Analisis menurut Perspektif Akidah Islam) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
Malay traditional treatment has long existed and has evolved in the Malay archipelago. A pilot survey which was conducted found a total of 18 traditional practitioners used mantra in their treatment. This paper examines the practice of mantra treatment and its relation from the perspective of Islamic faith. Efforts in treatment should be in line with the teaching of Islamic faith because the principles of monotheism in Islam need to be preserved from idolatry, superstition and delusion. As this research uses qualitative approach, library research and field studies were conducted to obtain data. Interviews and participant observation methods were also used. The study found that most of the practitioners of traditional treatments in Kedah were directly associated with asking for help from supernatural creatures such as genie, spirits and etc. Patients are advised to investigate carefully before getting treatment in order to avoid traditional treatments which are against the Islamic teaching.Keywords: practice mantra, traditional treatment, medicine men, faith